1979
DOI: 10.1111/j.1744-6570.1979.tb02340.x
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Among Data Sources, Response Bias, and Reliability and Validity of a Structured Job Analysis Questionnaire

Abstract: Research examined both the Position Analysis Questionnaire (PAQ) and the possible analyst sources for gathering job analysis information. 25 state government jobs were examined using job incumbents, supervisors, job analysts, and a comparison group of college students. Reliability and validity (judge convergence and prediction of present pay levels) information was determined for each of the four analyst categories. Results indicate that there is little difference between analyst sources, including students, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 13 publications
6
93
1
Order By: Relevance
“…The convergence of job analysis sources complements the literature on the common-knowledge effects in job analysis (Smith & Hakel, 1979). In those studies, considerable convergence has been found between trained analysts and untrained raters using limited information.…”
Section: Discussionmentioning
confidence: 90%
“…The convergence of job analysis sources complements the literature on the common-knowledge effects in job analysis (Smith & Hakel, 1979). In those studies, considerable convergence has been found between trained analysts and untrained raters using limited information.…”
Section: Discussionmentioning
confidence: 90%
“…We chose a relatively uncommon job for two reasons. First, it might preclude the activation of job stereotypes (DeNisi, Cornelius, & Blencoe, 1987;Smith & Hakel, 1979). Second, none of the expert consultants had previously determined the competencies of this job.…”
Section: Competency Modeling Taskmentioning
confidence: 99%
“…In a related study Smith and Hakel (1979) used the PAQ to obtain job analysis rating-from job incumbents, supervisors, trained job analysts, and students. …”
mentioning
confidence: 99%